The Analytic Hierarchy Process—An Exposition - Forman, Ernest H.; Gass, Saul I. (Operations Research, 2001)
This exposition on the Analytic Hierarchy Process (AHP) has the following objectives: (1) to discuss why AHP is a general methodology for a wide variety of decision and other applications, (2) to present brief descriptions of successful applications of the AHP, and (3) to elaborate on academic discourses relevant to the efficacy and applicability of the AHP vis-a-vis competing methodologies. We discuss the three primary functions of the AHP: structuring complexity, measurement on a ratio scale, and synthesis, as well as the principles and axioms underlying these functions. Two detailed applications are presented in a linked document at http://mdm.gwu.edu/FormanGass.pdf .